Analysis of the Prospect of Implementing Activity-Based Costing (ABC) in Governmental Organisations: A Study at the State Treasury Office Jakarta IV - Tri Priyatmo; Rusdi Akbar (Journal of Accounting and Investment, 2019)
This research aims to analyse the prospect of implementing Activity-Based Costing (ABC) at governmental organisations in Indonesia. The study aims to answer two research questions: how can we calculate the unit cost of products using the ABC method in a governmental organisation? (RQ1); and, what is the prospect of implementing ABC in governmental organisations? (RQ2). The study comprises qualitative research undertaken at one governmental organisation, that of the State Treasury Office (KPPN) Jakarta IV. The research reveals that the ABC method can be used to calculate the unit cost of products in KPPN Jakarta IV, and also to obtain a conceptual framework by which it is possible to conclude that the ABC method has a positive outlook as an analytical tool. However, one of the study’s research objects, the prospect of implementing the ABC method in this research, cannot be generalised for all governmental organisations in Indonesia. However, based on the results of this research, it can be stated that there is a shared understanding of the potential for the implementation of the ABC method in the future. This study is the first of its kind to investigate this topic and will yield new insight within the literature on the ABC method in Indonesia.